Refleksi Akur Sunda Wiwitan dan Pengakuan Negara - Gina Sabrina (CV Rewang Rencang, 2020)
Recognition becomes fundamental and important in the concept of human rights through recognition of the fulfillment of other rights can only be realized optimally. However, the recognition of believers in Indonesia found a steep road because it did not get recognition from the state. Instead of recognition, even the state is often an actor who imposes restrictions on the right to freedom of religion and belief through the policies and regulations it makes. These restrictions lead to structural injustices that discriminate over the fulfillment of other rights. This paper will reflect how the state's recognition of the flow of trust and the long road that must be taken by adherents to be recognized by the state. A long effort from a series of discriminatory events to gain recognition and restoration of his basic human rights.